PENERAPAN SEARCH ENGINE OPTIMIZATION PADA SITUS E-COMMERCE DALAM MENINGKATKAN RANKING - Riki Asrigo (Jurnal Informatika, 2023)
Search engine optimization (SEO) is a technique that improves website visibility in a search engine with targeted keywords. This study pertains to optimizing a website, to improve website rank and get first position in the search engine results page (SERP). The research’s SEO framework based on Hatab’s, generally consists of guidelines i.e: keywords analysis, indexing web sitemap to search engines directories, optimizing On-page and Off-page Factors, then measuring the results. This research was conducted using SEO techniques to an e-commerce website selling creative stationery in Indonesia, where the finding at pre-analysis step describes the website’s page rank has dropped significantly with small number of visitors. Website ranking and page position in Google SERP will be measured monthly as an optimization result. The result, SEO implementation can help boost the website rank from 53.901.125 to 8.635.332, put some webpages on the better page position of Google SERP, and help maintain the position in the long term. When further study needs to be done on increasing visitors and traffic, more keywords to optimize, improve website to mobile friendly, and expand to social media in building backlinks is highly suggested.